Manajemen Sumber Daya Manusia Dalam Program Cinta Lingkungan Bersh Dan Keren (Clbk) Di Dinas Lingkungan Hidup Kabupaten Luwu Timur (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to find out the process of resource management in the Clean and Cool Love for the Environment (CLBK) program at the Environmental Service of East Luwu Regency. There were 6 (six) informants in this study. Thos study used qualitative research method with a descriptive type of research. Data collection techniques were observation, interviews and documentation. The results showed 5 (five) human resource management processes in the Clean and Cool Love for the Environment (CLBK) program at the Environmental Service of East Luwu Regency, namely: 1) Human resource planning that through the mindset of office employees and cleaners and community mindset, 2) Recruitment that selected employees who were able to develop the CLBK program, 3) Selection that was the stage of collecting files to then be selected and accepted as employees, 4) Orientation that the processed of introducing the CLBK program to all elements of the East Luwu Regency community, and 5) Training and development provided understanding of 3R (reduce, reuse, and recycle), ecobrick. Keywords: Human Resource Management, Program